Social Phobia in Persian Adults with Stuttering - Ahmad Poormohammad; Zahra Ghayoumi-Anaraki; Maryam Faham; Davood Sobhani-Rad (Shiraz University of Medical Sciences, 2018)
Background: Stuttering is a communication disorder. It is expected that stuttering may have negative impact on individuals' mental and emotional health, which may affect their quality of life. Therefore, this paper aims to study components of social phobia inventory in Persian adults with stuttering and compare the likelihood (odds) of social phobia in the stuttering group to that in the control group. Methods: Using social phobia inventory, this case-control study compared social phobia in 33 adults with stuttering and 33 age-gender-education matched subjects with fluent speech. All the participants were 18 years or above. Results: Independent t-test showed that the total score of the social phobia inventory. Its fear component has significant statistical differences between group of adults with and without stuttering. Moreover, the adults with stuttering have over two times more social phobia symptoms than that in ones who don't. Conclusion: Our results suggest that social phobia should be considered in therapy programs for adults with stuttering. In addition to restructuring speech, a part of the treatment program should address people's social phobia, especially their feeling of fear, in order to curtail some of the negative consequences associated with stuttering.